Motor Deficits and Cerebellar Atrophy in Elovl5 Knock Out Mice - Hoxha, Eriola; Gabriele, Rebecca M. C.; Balbo, Ilaria; Ravera, Francesco; Masante, Linda; Zambelli, Vanessa; Albergo, Cristian; Mitro, Nico; Caruso, Donatella; Di Gregorio, Eleonora; Brusco, Alfredo; Borroni, Barbara; et al. (Frontiers in Cellular Neuroscience, 2017)
Spino-Cerebellar-Ataxia type 38 (SCA38) is caused by missense mutations in the very long chain fatty acid elongase 5 gene, ELOVL5. The main clinical findings in this disease are ataxia, hyposmia and cerebellar atrophy. Mice in which Elovl5 has been knocked out represent a model of the loss of function hypothesis of SCA38. In agreement with this hypothesis, Elovl5 knock out mice reproduced the main symptoms of patients, motor deficits at the beam balance test and hyposmia. The cerebellar cortex of Elovl5 knock out mice showed a reduction of thickness of the molecular layer, already detectable at 6 months of age, confirmed at 12 and 18 months. The total perimeter length of the Purkinje cell layer was also reduced in Elovl5 knock out mice. Since Elovl5 transcripts are expressed by Purkinje cells, whose dendrites are a major component of the molecular layer, we hypothesized that an alteration of their dendrites might be responsible for the reduced thickness of this layer. Reconstruction of the dendritic tree of biocytin-filled Purkinje cells, followed by Sholl analysis, showed that the distribution of distal dendrites was significantly reduced in Elovl5 knock out mice. Dendritic spine density was conserved. These results suggest that Elovl5 knock out mice recapitulate SCA38 symptoms and that their cerebellar atrophy is due, at least in part, to a reduced extension of Purkinje cell dendritic arborisation.